DATA MINING ANALYSIS TO DETERMINE EMPLOYEE SALARIES ACCORDING TO NEEDS BASED ON THE K-MEDOIDS CLUSTERING ALGORITHM - Alia Ahadi Argasah; Dudih Gustian (Informatika, Universitas Jenderal Soedirman, 2022)
A company to achieve its goals, one of the factors is the performance of employees according to company standards, employees will provide performance with company standards with the company's reciprocity on employees for example in the payroll aspect. The purpose of this research is to help companies with appropriate payroll so that it has a good impact on productivity, garment companies that produce various types of clothing require employees with sewing skills which are one of the most important aspects of production. The problem is in the production process that is hampered, one of the factors for decreasing employee performance is the incompatibility of salary with the abilities of employees. The k-medoids clustering method can help companies cluster employees according to the employee's ability value as a benchmark for wages, from 50 samples of employees and an assessment of the various skills possessed by employees so that the calculation results in the first cluster of 24 employees with a salary received Rp 100,000 per day, the second cluster the number of 16 employees with a salary received Rp 90,000 per day, the third cluster of 10 employees with a salary received Rp 80,000 per day. So it can be concluded that the clustering method can help companies with the right targets for grouping employee salaries according to the employee's abilities so that company productivity is not disturbed by declining employee performance or employee complaints over the incompatibility of payroll with employee abilities